No-Fault Compensation System and Restorative Justice in Medical Dispute Resolution: A Lesson from New Zealand for Indonesia - Sujana, I Kadek Eka; Fikri, Ahmad Ma’mum (Research Horizon, 2025)
Medical dispute resolution in Indonesia relies on a fault-based litigation model, which burdens patients with high evidentiary standards, stigmatizes physicians, and hinders systemic learning in healthcare. This article aims to explore the potential of integrating a no-fault compensation system with restorative justice as an alternative framework. The research adopts a normative juridical method combined with comparative legal analysis, using New Zealand’s accident compensation corporation as a primary comparative model. Findings indicate that Indonesia’s mechanism fails to ensure equitable remedies and often results in defensive medicine. New Zealand’s no-fault compensation system demonstrates efficiency and patient-centeredness. However, the no-fault compensation system alone may lack the relational repair component that restorative justice provides. The proposed hybrid no-fault restorative justice model combines material justice (compensation without proof of negligence) with relational justice (acknowledgement, apology, and trust restoration). This integrated approach is normatively consistent with Indonesia’s constitutional commitment to social justice and resonates with cultural values of deliberation. The hybrid no-fault restorative justice model could transform Indonesia’s health law from a punitive, adversarial paradigm into a preventative, restorative, and patient-centered system.